KAJIAN LITERATUR: PENINGKATAN HASIL BELAJAR MELALUI PENERAPAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI JENJANG SEKOLAH DASAR - Nadhiroh, Eka Sefti Ulfin; Mukarromah, Ifa Fatatul; Maftucha, Maftucha (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study examines the impact of the Contextual Teaching and Learning (CTL) model on improving student learning outcomes at the elementary school level, amidst the challenges of modern education that require effective, meaningful, and relevant learning processes in everyday life. A qualitative method with a systematic literature study was conducted by analyzing seven primary journal articles (2020–2025) from sources such as Google Scholar and Indonesian university repositories, using the keywords